臺灣學校領導研究與全球學術的連結：文獻計量分析 - 潘慧玲(Hui-Ling Wendy Pan); 陳文彥(Wen-Yan Chen) (Jiao yu ke xue yan jiu qi kan, 2021)
1. Background Systematic reviews may inform public policies and contribute to the building of a knowledge base. However, reviews of school leadership research are relatively rare in Taiwan. This study conducted a bibliometric review to analyze journal papers by Taiwanese scholars in the Scopus database published in the previous 20 years. The focus was to examine the connection between Taiwanese and global research on school leadership. 2. Research questions On the basis of the research background, four research questions were proposed: (1) What is the volume and growth trajectory of Taiwanese school leadership research? (2) What is the international visibility of Taiwanese school leadership research as revealed through citation analysis? (3) What are the main topics covered by Taiwanese school leadership research and how do they correspond to the global trend? (4) What is the intellectual structure of Taiwanese school leadership research and how do it connect with the global literature? 3. Theoretical framewo